DESAIN MODEL PEMBANGUNAN KESATUAN PENGELOLAAN HUTAN (KPH) DI KABUPATEN MAMUJU PROVINSI SULAWESI BARAT - . Supratman (Forestry Faculty of Universitas Hasanuddin, 2009)
The research aimed to designing model of forest unit management based on field situation. The research was conducted in Karossa and Topoyo District, Mamuju Regency, West Sulawesi Province. Collecting data was conducted with documentation study, Focus Group Discussion (FGD), interview and survey methods. Analysis was done that is Qualitative – Descriptive Analysis and Quantitative – Descriptive Analysis. Research outcome was obtained the model of forest unit management development linkage with the dynamics of community, IUPHHK, IPKTM, forest industry, resettlement project, and rural region development. To improving the forest unit management development, it needed convergence activity of institution that linkage with forest management. Key words: Model, Management, Forest, Forest Unit Management